MESSENGER survey of in situ low frequency wave storms between 0.3 and 0.7 AU. Issue 12 (16th December 2015) - Boardsen, S. A.; Jian, L. K.; Raines, J. L.; Gershman, D. J.; Zurbuchen, T. H.; Roberts, D. A.; Korth, H.
Abstract: MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) magnetometer data was surveyed between 0.3 and 0.7 AU from 6 June 2007 to 23 March 2011 for low‐frequency wave (LFW) storms, when the magnetometer was sampling at a rate of at least 2 s −1 . A total of 12, 197 LFW events were identified, of which 5506 lasted 10 min or longer. The events have a high degree of polarization, are circularly polarized, with wave vectors nearly aligned or antialigned with the interplanetary magnetic field (IMF) at frequencies in the vicinity of the proton cyclotron frequency. These events are observed about 6% of the time, preferentially associated with radially directed inward or outward IMF. Their occurrence rate and median duration do not change much with R, where R is the heliocentric radial distance. For a narrow‐frequency window in the solar wind frame, left‐handed storms in the spacecraft frame have a power drop off that is roughly proportional to R −3 which is consistent with a source close the Sun, while right‐handed storms have a power drop off roughly proportional R −1 which is not consistent with a source close to the Sun. The power in the left‐handed LFW storms is on average greater than the right‐handed ones by a factor of 3. In the solar wind frame, the wave frequency decreases from 0.13 to 0.04 Hz moving from 0.3 to 0.7 AU, but the frequency normalized by the local proton cyclotron frequency does not change much with the running median varying from 0.35 to 0.5. The normalized frequency band widths of the wave power spectra increase slightly with R, possibly associated with energy dissipation. Key Points: MESSENGER observations of low‐frequency storms are surveyed between 0.3 and 0.7 AU The occurrence rate of these storms is about 6 times larger than that of previous studies The radial power variation of the right handed storms is not consistent with a source near the Sun